Caracterização molecular de genes do sistema imune de búfalo - Borges, Mariana Maciel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In mammals, genes related to immune response to pathogens are organized in a genomic region named Major Histocompatibility Complex (MHC). MHC genes are also involved in mate-choice, occurrence of spontaneous abortions and maintenance of pregnancy. The existence of a genomic library, constructed with buffalo genome, allows the characterization of MHC genes, providing sources for understanding the mechanisms involved in resistance/susceptibility to diseases and in reproduction, contributing for annotation of these genes on buffalo genome. To determine the molecular structure of buffalo immune system genes, the present study aimed to identify and characterize clones containing class IIb markers from a buffalo genomic library. Selection of clones was performed by PCR technique, according to three-dimensional system (superpool, singlepool, row/column system) in which clones are arranged. To identify the clones were used 21 class IIb markers, previously mapped on buffalo chromosome 2. Among the 33.792 clones evaluated, three clones were identified for the MHC markers 11.05, 12.05, 13.00 and DMA. These clones were then purified and sequenced by pyrosequencing, presenting insert size ranging from 26 to 117 Kb. Each clone sequence were aligned with two bovine genome assemblies (UMD_3.1 and Btau_4.6.1), where the most significant alignments were identified with the corresponding sequences to BTA23. Sequences of both clones showed a greater coverage in UMD_3.1 assembly. Four genes were predicted for clone A/17 DNA sequence (H2B, DMB, DMA and BRD2), and one gene (VPS52) was predicted for clone I/09 sequence. Each gene had the number and size of exons and introns determined. The identification of repetitive sequences showed that 49,3% of clone A/17 sequence and 46,3% of clone I/09 sequence are represented by transposable elements. Furthermore, small RNA sequences were identified in both clones ...

Em mamíferos, os genes relacionados à resposta imune do hospedeiro à patógenos encontram-se organizados na região genômica denominada Complexo Principal de Histocompatibilidade (MHC). Os genes da região MHC também estão envolvidos na escolha do parceiro para acasalamento, na ocorrência de abortamentos espontâneos e na manutenção da gestação. A disponibilidade de uma biblioteca genômica construída com o genoma de búfalo torna possível a caracterização molecular dos genes dessa região. Tal caracterização permitirá o entendimento dos mecanismos envolvidos na resistência/suscetibilidade à doenças e na reprodução em búfalos, além de contribuir para a anotação desses genes no genoma bubalino. Visando determinar a estrutura molecular dos genes do sistema imune de búfalo, o presente trabalho teve como objetivo a identificação e a caracterização de clones da biblioteca genômica de búfalo contendo marcadores da classe IIb. A seleção dos clones foi realizada por meio da tecnologia de PCR, segundo o sistema de organização tridimensional (superpool, singlepool e sistema linha/coluna) no qual os clones da biblioteca se encontram organizados. As reações de PCR foram realizadas utilizando 21 marcadores da classe IIb mapeados no cromossomo 2 de búfalo. Dentre os 33.792 clones avaliados, foram identificados três clones positivos para quatro marcadores da classe IIb, sendo eles: 11.05, 12.05, 13.00 e DMA. Após a seleção, os clones foram purificados e sequenciados via pirosequenciamento, onde apresentaram tamanho de inserto variando de 26 a 117 Kb. As sequências obtidas para cada um dos clones foram alinhadas com as duas versões de anotação do genoma bovino (UMD_3.1 e Btau_4.6.1), onde os alinhamentos mais significativos foram identificados com as sequências correspondentes do cromossomo BTA23. Os resultados obtidos mostraram que as sequências de ambos os clones ...
Keywords: Búfalo; Genomas; Genes; Genômica; Genetica molecular; Genetica animal; Molecular genetics